A fully coupled thermo‐viscoelastic finite element model for self‐folding shape memory polymer sheets. Issue 16 (20th May 2017) - Mailen, Russell W.; Dickey, Michael D.; Genzer, Jan; Zikry, Mohammed A.
ABSTRACT: The thermo‐mechanical response of heat activated shape memory polymers (SMPs) has been investigated using a thermo‐viscoelastic finite element analysis that accounts for external and internal heat sources. SMPs can be thermally stimulated by external heat sources, such as temperature and surface heat flux, or from internal viscous heating. Viscous heating can significantly affect the response of SMP sheets by increasing the temperature during pre‐strain, which accelerates stress relaxation. This stress relaxation results in a slower shrinking rate when the SMP is reheated. Viscous heating also causes an increase in temperatures during unconstrained recovery. The predicted results elucidate how the coupled thermo‐mechanical loading conditions affect folding and unfolding of SMP sheets in response to localized heating in a hinged region. A parametric study of sheet thickness, hinge width, degree of pre‐strain, and hinge surface temperature is also conducted. The validated results can provide guidelines for the design of functional, self‐folding structures. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2017, 55, 1207–1219 Abstract : The thermo‐mechanical response of thermally activated shape memory polymers (SMPs) is investigated using finite element analysis (FEA) with a thermo‐viscoelastic material model. The SMP can be heated by external sources or internal viscous heating. The modeling results indicate how the coupled thermo‐mechanical loading conditions affect the folding and unfolding of SMP sheets in response to localized heating. These results can be used to set guidelines for the design of functional, self‐folding SMP structures.